Di-μ-chlorido-bis[(2,2′:6′,2′′-terpyridine-κ3N,N′,N′′)copper(II)] bis(trifluoromethanesulfonate) - Rafael A. Adrian (International Union of Crystallography, 2021)
In the centrosymmetric title complex, [Cu2Cl2(C15H11N3)2](CF3O3S)2, the CuII metal center is fivefold coordinated by two chloride ions and three nitrogen atoms of the terpyridine ligand in a distorted square-pyramidal geometry; two trifluoromethanesulfonate ions complete the outer coordination sphere. π–π stacking interactions between the pyridyl rings in adjacent molecules contribute to the alignment of the complexes in columns along the a-axis. This structure represents the first example of a binuclear dication of formula [Cu(terpy)2Cl2]2+ with trifluoromethanesulfonate as counter-ions.